Retrograde Extraperitoneal Laparoscopic Prostatectomy (RELP). A Prospective Study about 1,000 Consecutive Patients, with Oncological and Functional Results - Dubernard, Pierre; Chaffange, Pierre; Pacheco, Philippe; Pricaz, Elie; Vaziri, Nader; Vinet, Maxime; Chalabreysse, Philippe; Rochat, Charles-Henry; Ficheur, Grégoire; Chazard, Emmanuel (Urology Journal, 2021)
Purpose: Usual laparoscopic surgery of localized prostate cancer uses antegrade dissection. We describe and evaluate the original RELP (Retrograde Extraperitoneal Laparoscopic Prostatectomy). Materials and Methods: A prospective cohort of 1005 patients with clinical localized cancer prostate were operated from December 1999 to September 2013, in Lyon (France), and followed up to 172 months (median: 60 months). Patients encountered a RELP procedure, a totally extra-peritoneal approach with a retrograde dissection from the apex to the bladder neck, and ascending dissection of the erectile neurovascular bundles, facilitated by the 30° optic telescope. Adjunctive treatments were: immediate radiotherapy (9.2%), salvage radiotherapy (13.4%), androgen deprivation therapy (10.8%), chemotherapy (1.4%), no treatment (75.8%). Results The mean age was 63.4, the Gleason score was 4+3 or worse in 24.9%, there were 2.3% unifocal tumors. The pathology stages were pT2A (8.71%), pT2B (2.80%), pT2C (69.0%), pT3A (13.1%), and pT3B (6.41%). There were 60.8% negative margins (R0) in total (90.1% for basal locations, and 75.8% for apical locations). The mean operating time was 115 minutes for the last 100 patients. The BPFSR (biological progression free survival rate, PSA≤0.10 ng/ml) was 71.9% at 5 years, and 61.4% at 10 years. The cancer specific survival rate was 99.4% at 5 years, and 98.3% at 10 years. After 12 months, 88.6% of patients did not require an incontinence pad, and 67.0% retained the pre-operative quality of their erection. Conclusion: RELP yields good oncologic results and quality of life, as good as robot-assisted surgery.